Flame-retardant interface self-adapting electrolyte suitable for carbon-based or alloy negative electrode and application thereof
Patent Information
- Application Number
- CN202611084677.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
并且,本发明所采用的纯磷酸酯溶剂为解决传统碳酸酯/醚类共溶剂带来的易燃隐患等安全问题提供了新途径
[0017]优选地,所述负极活性材料的制备方法包括:将溶剂与铋盐、有机配体混合均匀,得到混合液;将所述混合液于110~130℃加热20~28小时,得到铋金属有机框架前驱体;将所述铋金属有机框架前驱体进行洗涤和干燥;将含氮掺杂剂和干燥后的所述铋金属有机框架前驱体分别置于管式炉的上游和下游,在惰性气体下1~3℃/min升温至700~900℃煅烧2~4h,冷却,得所述负极活性材料。
Smart Images

Figure CN123018093A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of potassium-ion battery technology, specifically to a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, its preparation method, and its application. Background Technology
[0002] Potassium-ion batteries have been a central focus of electrochemical energy storage research in recent years due to the abundance and sustainable supply of potassium resources. Carbon reduction and renewable energy policies demand longer lifespans, higher energy efficiency, and lower maintenance costs for energy storage systems, while also prioritizing safety and environmental impact. This trend has endowed potassium-ion batteries with extremely broad application prospects and profound economic benefits. The electrolyte, as one of the most crucial chemical components of a battery, plays a vital role in long-term cycling, influencing capacity retention, coulombic efficiency, and safety margins.
[0003] Graphitized carbon, with its advantages of abundant raw material sources and relatively controllable costs, has become a widely used and mature commercial anode material in potassium-ion batteries. However, graphitized carbon faces inherent bottlenecks such as low theoretical specific capacity and sluggish potassium insertion / extraction kinetics, making it difficult to meet the needs of next-generation high-energy-density energy storage systems. To overcome this capacity limitation, alloy materials have emerged as leaders due to their superior potassium storage capacity. Alloy materials exhibit excellent potassium storage performance, and when combined with metal-organic frameworks at the nanoscale, they demonstrate even more efficient interfacial charge transfer kinetics. In particular, bismuth-based anode materials are considered highly promising candidates due to their suitable redox potential and ultra-high mass / volume specific capacity; however, bismuth-based and other alloy materials inevitably suffer from significant volume expansion during charge and discharge.
[0004] Potassium-ion battery electrolytes are typically composed of potassium salts and non-aqueous organic solvents, with their core function being the efficient transport of large potassium ions between the positive and negative electrodes. While ether-based electrolytes can effectively mitigate the co-intercalation effect of graphite anodes and improve rate performance, they suffer from poor oxidation resistance, high volatility, and system instability, readily decomposing at the positive electrode. Furthermore, traditionally used carbonate-based electrolytes, although possessing some ion transport capabilities at room temperature, often result in an SEI film at the negative electrode rich in fragile organic components, easily rupturing during repeated potassium ion intercalation and deintercalation. Additionally, the solvent itself is highly flammable, posing serious safety hazards. Therefore, when selecting an electrolyte, a comprehensive consideration of factors such as interfacial compatibility, oxidation resistance, and flame retardant safety is necessary. In contrast, battery systems using pure phosphate ester organic solvents as electrolytes offer a degree of interfacial stability, with relatively controllable side reactions.
[0005] Similar to lithium-ion batteries, the interfacial chemical stability of potassium-ion batteries is significantly affected by the electrolyte coordination environment. To overcome side reactions caused by traditional solvents, the battery field has been actively exploring novel electrolyte formulation strategies. Studies have shown that high-concentration electrolyte strategies effectively improve the reversibility of potassium-ion batteries under long-term cycling. However, it is worth noting that such high-concentration electrolyte systems are not only costly but also exhibit a sharp increase in viscosity, leading to significant degradation in ionic conductivity and discharge rate performance at room temperature. This challenge indicates that although some progress has been made in interfacial modification, achieving superior cycling performance of potassium-ion battery anodes under low salt concentrations or conventional conditions remains a problem requiring continuous research and improvement. Future research may need to focus on finding more innovative and feasible solvation structure control schemes to overcome the contradiction between material volume expansion and SEI stability. Summary of the Invention
[0006] The purpose of this invention is to at least solve one of the technical problems existing in the prior art, and to provide a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, its preparation method and application.
[0007] To address the aforementioned technical challenges, this invention uses commercially available graphite carbon as a benchmark and a newly prepared nano-sized bismuth-based alloy composite material (Bi NPs / NC) as the core to construct an electrolyte system more suitable for gold anodes. By improving the chemical composition of the electrolyte, it enables faster and more repeatable establishment of a stable SEI at room temperature, significantly enhancing battery durability and demonstrating considerable application potential. This invention combines the bismuth-based alloy with a metal-organic framework for nano-sizing. This strategy not only effectively buffers volumetric stress during cycling but also endows the system with more efficient interfacial charge transfer kinetics. Furthermore, the pure phosphate ester solvent used in this invention provides a new approach to address safety issues such as flammability hazards associated with traditional carbonate / ether co-solvents.
[0008] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, the electrolyte comprising potassium salts, phosphate ester organic solvents and fluorinated borate ester additives; The phosphate ester organic solvent contains a polar phospho group, which is used for the dissociation and coordination of potassium ions; The reduction decomposition potential of the fluorinated borate ester additive is higher than that of the phosphate ester organic solvent. In the low potential region of the negative electrode, the fluorinated borate ester additive can preferentially reduce and decompose on the carbon-based or alloy negative electrode surface to form a solid electrolyte interface film compared with the phosphate ester organic solvent.
[0009] Preferably, the potassium salt is an organic potassium salt that is a single electrolyte salt, and the anionic radius of the organic potassium salt is greater than the chloride ion radius; The potassium salt can undergo reduction decomposition on the surface of the carbon-based or alloy anode, and together with the decomposition products of the fluorinated borate ester additive, form a solid electrolyte interface film rich in inorganic components on the surface of the carbon-based or alloy anode.
[0010] Preferably, the potassium salt is selected from any one of potassium difluorosulfonylimide, potassium trifluoromethanesulfonate, potassium difluorophosphate, potassium tetrafluoroborate, potassium difluoroborate bis(oxalate) and potassium difluoroborate bis(oxalate). The general structural formula of the phosphate ester organic solvent is P(=O)-(OR3)3, wherein R3 is selected from any one of methyl, ethyl, propyl, butyl, monofluoromethyl, difluoromethyl, trifluoromethyl and phenyl; The fluorinated borate ester additives are selected from at least one of tris(hexafluoroisopropyl) borate, tris(2,2,3,3-tetrafluoropropyl) borate, tris(pentafluorophenyl) borate, tris(2,2,3,3,3-pentafluoropropyl) borate, and tris(2,2,2-trifluoroethyl) borate.
[0011] Preferably, the total mass of potassium salt, phosphate ester organic solvent and fluoroboronic acid ester additive is 100% as the standard, wherein the mass percentage of potassium salt is 24-35 wt%, the mass percentage of phosphate ester organic solvent is 63-75 wt%, wherein the organic solvent is selected from phosphate ester organic solvent, and the mass percentage of fluoroboronic acid ester additive is 0.1-2.5 wt%.
[0012] Secondly, the present invention provides a method for preparing the electrolyte, characterized by comprising the following steps: Dehydration is achieved by using phosphate ester organic solvents and fluoroboronic acid ester additives; Dry the potassium salt at 60~80℃; The electrolyte is obtained by mixing the phosphate ester organic solvent with the potassium salt and the fluorinated borate ester additive until completely dissolved.
[0013] Thirdly, the present invention provides the application of the electrolyte in a potassium-ion battery, wherein the negative electrode material of the potassium-ion battery is an alloy negative electrode material or a carbon-based material.
[0014] Fourthly, the present invention provides a potassium-ion battery, which includes a negative electrode and the electrolyte; The negative electrode includes a negative electrode active material, which is a bismuth nanoparticle composite material coated with a nitrogen-doped carbon network. The boron in the fluorinated borate ester additive can form a BN coordination relationship with the nitrogen in the negative electrode active material, thereby forming a solid electrolyte interface film in situ on the negative electrode surface.
[0015] Preferably, the negative electrode active material is prepared by calcining a bismuth metal-organic framework precursor and a nitrogen-containing dopant under an inert atmosphere; The raw materials for preparing the bismuth metal-organic framework precursor include bismuth salts, organic ligands, and solvents. The bismuth salt is selected from at least one of bismuth nitrate, bismuth chloride, bismuth acetate, and basic bismuth carbonate; The organic ligand is selected from at least one of pyromellitic acid, terephthalic acid, 2-methylimidazolium and pyromellitic acid; The solvent is selected from at least one of methanol, ethanol, isopropanol, N,N-dimethylformamide, and N,N-dimethylacetamide; The nitrogen-containing dopant is selected from at least one of cyanoguanidine, melamine, urea, and thiourea.
[0016] Preferably, In the negative electrode active material, with the total mass of the bismuth salt and organic ligand as 100%, the mass percentage of the bismuth salt is 10~25wt%, and the mass percentage of the organic ligand is 75~90wt%. The amount of nitrogen-containing dopant added is 24-48 wt% of the mass of the bismuth metal-organic framework precursor.
[0017] Preferably, the preparation method of the negative electrode active material includes: mixing a solvent with a bismuth salt and an organic ligand to obtain a mixed solution; heating the mixed solution at 110~130℃ for 20~28 hours to obtain a bismuth metal-organic framework precursor; washing and drying the bismuth metal-organic framework precursor; placing a nitrogen-containing dopant and the dried bismuth metal-organic framework precursor at the upstream and downstream of a tube furnace, respectively, and calcining at 700~900℃ for 2~4 hours under an inert gas at a rate of 1~3℃ / min, followed by cooling to obtain the negative electrode active material.
[0018] This invention has at least one of the following beneficial effects: 1. This invention provides an electrolyte formed from potassium salts, phosphate ester organic solvents, and fluorinated borate ester additives. Compared with traditional commercial electrolytes, the electrolyte of this invention not only has excellent intrinsic flame retardant properties, but also exhibits superior cycle performance in stabilizing the negative electrode. The electrolyte of this invention innovatively introduces fluorinated borate ester additives as film-forming additives, which preferentially undergo interfacial reactions in the low potential region, promoting the early formation of a dense and fluorine-rich SEI film on the electrode surface, effectively inhibiting the continuous reduction and decomposition of the electrolyte. The organic solvent used in this invention ensures sufficient dissolution of the electrolyte, and the SEI film formed on the electrode surface is more stable. The electrolyte of this invention has a simplified composition, significant synergistic effect, and excellent compatibility with carbon-based and alloy-based negative electrode systems, making it suitable for constructing novel potassium-ion batteries that combine high safety and long lifespan.
[0019] 2. This invention provides a potassium-ion battery. Compared to the graphite or soft carbon materials widely used as negative electrodes in traditional commercial potassium-ion batteries, the bismuth-based alloy negative electrode (Bi NPs / NC) selected in this invention can store potassium through alloying / dealloying reactions, exhibiting a theoretical specific capacity far exceeding that of carbon-based materials. Furthermore, by utilizing the electron-deficient boron centers in the fluoroboron ester additive to generate a strong "BN" coordination with the electron-rich nitrogen sites in the negative electrode carbon substrate, a tough and highly elastic solid electrolyte interface (SEI) film is constructed in situ on the dramatically expanding bismuth alloy surface. Therefore, this battery system not only possesses flame-retardant properties but also perfectly overcomes the technical bottlenecks of easy pulverization of alloy negative electrodes and easy co-intercalation of pure phosphate esters, significantly improving the long-term cycle stability and capacity retention of potassium-ion batteries. Attached Figure Description
[0020] Figure 1 X-ray diffraction pattern of Bi NPs / NC; Figure 2 TEM image of Bi NPs / NC obtained at 500 nm; Figure 3 To characterize the microstructure of the electrode surface after cycling, the electrolyte prepared in Comparative Example 2 was applied to the Bi NPs / NC prepared in Example 9. Figure 4 To characterize the microstructure of the electrode surface after cycling, the electrolyte prepared in Example 1 was applied to the Bi NPs / NC prepared in Example 9. Figure 5 Comparison of the coulombic efficiency of potassium-copper half-cells prepared in Comparative Example 2, Example 1, Example 2, Example 3 and Example 4 under charge-discharge conditions of 0.01-1V, 30℃, and 0.5C. Figure 6The deposition and stripping curves of potassium-copper half-cells prepared in Comparative Example 2, Example 1, Example 2, Example 3 and Example 4 are shown under the conditions of 0.01-1V, 30℃ room temperature, and 0.5C charge-discharge. Figure 7 Comparison of the cycle performance of potassium batteries using soft carbon material prepared in Comparative Example 3 as the negative electrode at 0.01-3V, 30℃, and 50mA / g, with electrolytes prepared in Comparative Example 1, Comparative Example 2, Example 1 and Example 2 as the electrolytes prepared in Comparative Example 3, Comparative Example 2, Example 1 and Example 2 as the electrolytes prepared in Comparative Example 3, Comparative Example 2, Example 1 and Example 2 as the electrolytes prepared in Comparative Example 3, Comparative Example 2, Comparative Example 3 ... and Example 3 as the electrolytes prepared in Comparative Example 3, Comparative Example 2 and Example 3 as the electrolytes prepared in Comparative Example 3, Comparative Example 2 Figure 8 The charge-discharge curves of a potassium battery using the electrolyte prepared in Example 1 at 0.01-3V, 30℃, and 50mA / g current density, with the soft carbon material prepared in Comparative Example 3 as the negative electrode. Figure 9 Comparison of the cycling performance of potassium batteries prepared in Comparative Examples 1, 2, 1, 2, 5, 6, 7, and 8 at 0.01-3V, 30℃, and 50mA / g current density, with Bi NPs / NC prepared in Example 9 as the negative electrode. Figure 10 The charge-discharge curves of a potassium battery prepared in Example 9 with Bi NPs / NC as the negative electrode under the electrolyte prepared in Example 1 at 0.01-3V, 30℃, and 50mA / g current density. Figure 11 The graph shows a comparison of the cycle performance of potassium batteries using the electrolyte prepared in Example 1 at 0.01-3V, 30℃, and 50mA / g current density, with Bi NPs / NC prepared in Example 9 and soft carbon material prepared in Comparative Example 3 as the negative electrode. Detailed Implementation
[0021] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0022] One embodiment of the present invention provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, the electrolyte comprising potassium salt, phosphate ester organic solvent and fluorinated borate ester additive; The phosphate ester organic solvent contains a polar phospho group, which is used for the dissociation and coordination of potassium ions; The reduction decomposition potential of the fluorinated borate ester additive is higher than that of the phosphate ester organic solvent. In the low potential region of the negative electrode, the fluorinated borate ester additive can preferentially reduce and decompose on the carbon-based or alloy negative electrode surface to form a solid electrolyte interface film compared with the phosphate ester organic solvent.
[0023] The phosphate ester organic solvent used in this invention possesses good stability, a high flash point, and a high dielectric constant, enabling it to effectively dissolve potassium salts. Furthermore, its highly polar phosphorus-oxygen structure exhibits excellent dissociation and strong coordination ability towards large-radius potassium ions, ensuring not only efficient ion conduction but also endowing the system with outstanding antioxidant properties. The trace amounts of fluorinated borate ester additives introduced in this invention provide excellent film-forming protection for the anode material. They preferentially reduce and decompose on the anode surface compared to the phosphate ester solvent, constructing a solid electrolyte interphase (SEI) film rich in inorganic components. This effectively prevents the co-intercalation of pure phosphate ester solvent molecules and improves the compatibility between the electrolyte and the anode material.
[0024] In some embodiments, the potassium salt is an organic potassium salt that serves as a single electrolyte salt, wherein the anionic radius of the organic potassium salt is greater than that of the chloride ion; the potassium salt can undergo reduction decomposition on the surface of the carbon-based or alloy anode, and together with the decomposition products of the fluorinated borate ester additive, form a solid electrolyte interface film rich in inorganic components on the surface of the carbon-based or alloy anode.
[0025] This invention breaks away from the conventional approach of relying on complex mixed solvents and dual-salt systems for electrolytes. The potassium salt used in this invention is an organic potassium salt, which has a large anionic radius, a relatively dispersed charge distribution, and strong electron delocalization. This reduces the lattice energy of the potassium salt, weakens the association between cations and anions, increases solubility, improves electrolyte conductivity, and also contributes to improved electrochemical and thermal stability. This invention preferentially uses this specific organic potassium salt as the single electrolyte salt, fully leveraging its high dissociation characteristics to give the electrolyte system excellent intrinsic conductivity, resulting in an electrolyte with high safety, high ionic conductivity, and good compatibility with both positive and negative electrodes. The organic potassium salt of this invention readily dissociates in the electrolyte, not only imparting excellent ionic conductivity to the system but also preferentially undergoing reduction decomposition on the carbon-based negative electrode surface, participating in the construction of a robust interfacial protective film rich in inorganic components. This tough inorganic protective film effectively blocks the co-intercalation of polar solvent molecules, significantly inhibiting continuous electrolyte consumption and negative electrode pulverization.
[0026] In some embodiments, the lowest unoccupied molecular orbital energy level of the fluorinated borate ester additive is lower than that of the lowest unoccupied molecular orbital energy level of the phosphate ester organic solvent, and the fluorinated borate ester additive can preferentially decompose on the carbon-based or alloy negative electrode surface to form a solid electrolyte interface film containing fluorine.
[0027] This invention introduces a highly efficient film-forming additive with a lower orbital energy level into a phosphate ester organic solvent as the electrolyte solvent, resulting in advantages such as high safety, high conductivity, and improved battery cycle performance. A single-salt, single-solvent electrolyte is synthesized using a single potassium salt combined with a single phosphate ester organic solvent, which not only significantly reduces the solution preparation cost for industrial mass production but also completely eliminates the flammability hazards associated with traditional carbonate / ether co-solvents, endowing potassium-ion batteries with extremely high safety performance.
[0028] In some embodiments, the potassium salt comprises only a main salt, wherein the main salt is selected from any one of potassium difluorosulfonylimide, potassium trifluoromethanesulfonate, potassium difluorophosphate, potassium tetrafluoroborate, potassium difluoroborate bis(oxalate) and potassium difluoroborate bis(oxalate).
[0029] The bis(fluorosulfonyl)imide anion (FSI-) in potassium bis(fluorosulfonyl)imide (KFSI) possesses a highly delocalized charge distribution and extremely low lattice energy. It readily dissociates in the electrolyte, not only imparting excellent ionic conductivity to the system but also preferentially undergoing reduction decomposition on the carbon-based anode surface, participating in the construction of a robust interfacial protective film rich in inorganic components. This tough inorganic protective film effectively blocks the co-intercalation of polar solvent molecules, significantly inhibiting continuous electrolyte consumption and anode structural pulverization. The sulfofluorine bond (SF) within it easily breaks under cathodic polarization, contributing to interface stability and directly promoting the formation of a highly efficient passivation component containing KF (potassium fluoride). While potassium hexafluorophosphate (KPF6) has certain advantages in preventing corrosion of aluminum foil current collectors, its thermal stability and hydrolysis resistance are extremely poor, readily decomposing to produce destructive hydrofluoric acid (HF), which not only severely corrodes the electrode interface but also accelerates battery performance degradation at high temperatures.
[0030] In some embodiments, the general structural formula of the phosphate ester organic solvent is P(=O)-(OR3)3, wherein R3 is selected from any one of methyl, ethyl, propyl, butyl, monofluoromethyl, difluoromethyl, trifluoromethyl and phenyl; In some embodiments, the fluorinated borate ester additive is selected from at least one of tris(hexafluoroisopropyl) borate, tris(2,2,3,3-tetrafluoropropyl) borate, tris(pentafluorophenyl) borate, tris(2,2,3,3,3-pentafluoropropyl) borate, and tris(2,2,2-trifluoroethyl) borate.
[0031] In some embodiments, the total mass of potassium salt, phosphate ester organic solvent and fluoroboronic acid ester additive is 100% as a standard, wherein the mass percentage of potassium salt is 24-35 wt%, the mass percentage of phosphate ester organic solvent is 63-75 wt%, wherein the organic solvent is selected from phosphate ester organic solvents, and the mass percentage of fluoroboronic acid ester additive is 0.1-2.5 wt%.
[0032] Another embodiment of the present invention provides a method for preparing the electrolyte, comprising the following steps: Dehydration is achieved by using phosphate ester organic solvents and fluoroboronic acid ester additives; Dry the potassium salt at 60~80℃; The electrolyte is obtained by mixing the phosphate ester organic solvent with the potassium salt and the fluorinated borate ester additive until completely dissolved.
[0033] The electrolyte of this invention uses simple raw materials and has a simple preparation method. Compared with traditional electrolytes, the electrolyte of this invention has the advantages of high safety, high conductivity, and improved battery cycle performance.
[0034] In some embodiments, the dehydration and drying are carried out in a glove box.
[0035] In some embodiments, the drying temperature is 80°C.
[0036] In some embodiments, the humidity inside the glove box is less than 0.01 ppm.
[0037] In some embodiments, the method for removing water is selected from any one or more of distillation, addition of molecular sieves, and addition of drying substances.
[0038] In some embodiments, the dried material is selected from any one or more of calcium hydride, activated carbon, anhydrous calcium oxide, lithium hydride, calcium chloride, phosphorus pentoxide, alkali metals, and alkaline earth metals.
[0039] Preferably, the mixing method is stirring, and the stirring time is 12 hours. In another embodiment of the present invention, the electrolyte is used in a potassium-ion battery, wherein the negative electrode material of the potassium-ion battery is an alloy negative electrode material or a carbon-based material.
[0040] The electrolyte of this invention exhibits superior cycle performance. When applied to potassium-ion batteries using carbon-based or alloy-based materials as negative electrodes, it significantly improves the battery's electrochemical performance, particularly its cycle performance. Compared to conventional electrolytes, the electrolyte of this invention offers advantages such as high safety, high conductivity, and enhanced battery cycle performance. The electrolyte of this invention enables potassium-ion batteries to achieve excellent cycle performance and capacity retention, significantly outperforming conventional potassium-ion batteries made with commercially available electrolytes.
[0041] In some embodiments, the potassium-ion battery is a coin-type potassium battery with a bismuth alloy negative electrode. The working electrode of the coin-type potassium battery is a bismuth alloy negative electrode, the counter electrode is a potassium sheet, a glass fiber separator is placed between the working electrode and the counter electrode, and the electrolyte is the single-salt potassium battery electrolyte.
[0042] Another embodiment of the present invention provides a potassium-ion battery, which includes the electrolyte described above as a negative electrode; The negative electrode includes a negative electrode active material, which is a bismuth nanoparticle composite material coated with a nitrogen-doped carbon network. The boron in the fluorinated borate ester additive can form a BN coordination relationship with the nitrogen in the negative electrode active material, thereby forming a solid electrolyte interface film in situ on the negative electrode surface.
[0043] This invention utilizes the strong coordination between electron-deficient boron centers in fluoroboronate additives and electron-rich nitrogen sites in the carbon substrate of the negative electrode to create a tough and highly elastic solid electrolyte interface (SEI) film in situ on the surface of the rapidly expanding bismuth alloy. Furthermore, compared to the graphite or soft carbon materials widely used as negative electrodes in traditional commercial potassium-ion batteries, the bismuth-based alloy negative electrode (Bi NPs / NC) selected in this invention can store potassium through alloying / dealloying reactions, exhibiting a theoretical specific capacity far exceeding that of carbon-based materials. In actual assembled potassium-ion batteries, it imparts extremely high reversible discharge specific capacity, achieving a leapfrog improvement in potassium storage capacity. This battery system not only possesses flame-retardant properties but also perfectly overcomes the technical bottlenecks of easy pulverization of alloy negative electrodes and easy co-intercalation of pure phosphate esters, significantly improving the long-term cycle stability and capacity retention of potassium-ion batteries. Compared with traditional electrolytes, the electrolyte of this invention, through the synergistic optimization of organic solvents and additives, can achieve higher capacity retention in alloy-type anode systems, while improving stability during long-term cycling, which is significantly better than potassium-ion batteries made with traditional commercial electrolytes.
[0044] In some embodiments, the negative electrode active material is prepared by calcining a bismuth metal-organic framework precursor and a nitrogen-containing dopant under an inert atmosphere; The raw materials for preparing the bismuth metal-organic framework precursor include bismuth salts, organic ligands, and solvents. The bismuth salt is selected from at least one of bismuth nitrate, bismuth chloride, bismuth acetate, and basic bismuth carbonate; The organic ligand is selected from at least one of pyromellitic acid, terephthalic acid, 2-methylimidazolium and pyromellitic acid; The solvent is selected from at least one of methanol, ethanol, isopropanol, N,N-dimethylformamide, and N,N-dimethylacetamide; The nitrogen-containing dopant is selected from at least one of cyanoguanidine, melamine, urea, and thiourea.
[0045] The bismuth alloy anode of this invention successfully overcomes the structural pulverization problem of high-capacity metal alloy anodes. While ensuring high interface stability, it fully leverages the high theoretical specific capacity advantage of bismuth alloy materials in potassium storage. Compared to carbon-based materials with lower capacity due to limitations in potassium storage mechanisms, the battery energy density of this invention represents a significant leap forward, demonstrating greater commercial value in energy storage.
[0046] In some embodiments, in the negative electrode active material, with the total mass of the bismuth salt and organic ligand as 100%, the mass percentage of the bismuth salt is 10-25 wt%, and the mass percentage of the organic ligand is 75-90 wt%. The amount of nitrogen-containing dopant added is 24-48 wt% of the mass of the bismuth metal-organic framework precursor.
[0047] In some embodiments, the preparation method of the negative electrode active material includes: mixing a solvent with a bismuth salt and an organic ligand to obtain a mixed solution; heating the mixed solution at 110~130℃ for 20~28 hours to obtain a bismuth metal-organic framework precursor; washing and drying the bismuth metal-organic framework precursor; placing a nitrogen-containing dopant and the dried bismuth metal-organic framework precursor at the upstream and downstream of a tube furnace, respectively, and calcining at 700~900℃ for 2~4 hours under an inert gas at a rate of 1~3℃ / min, followed by cooling to obtain the negative electrode active material.
[0048] This invention utilizes bismuth metal-organic frameworks (Bi-MOFs) as precursors for vapor-phase calcination to uniformly confine highly active bismuth nanoparticles (Bi NPs) within a three-dimensional porous carbon framework. This unique structure provides ample physical buffer space for the volume expansion of bismuth particles and also constructs high-speed electron and ion transport channels, greatly improving the reaction kinetics of the electrode.
[0049] The present invention will be further described in detail below with reference to specific embodiments, but the present invention is not limited to the following specific embodiments.
[0050] Example 1 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) was selected as the organic solvent for phosphate esters, and tri(2,2,2-trifluoroethyl) borate (TTFEB) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, 3A molecular sieve was added to TEP and TTFEB respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0051] (3) Weigh 29.4% KFSI, 70.4% TEP and 0.2% TTFEB according to their mass percentages to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix them thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0052] Example 2 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) was selected as the phosphate ester organic solvent, and tri(2,2,2-trifluoroethyl) borate (TTFEB) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, the molecular sieve was added to TEP and TTFEB respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0053] (3) Weigh 29.3% KFSI, 70.2% TEP and 0.5% TTFEB according to their mass percentages to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix them thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0054] Example 3 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) was selected as the phosphate ester organic solvent, and tri(2,2,2-trifluoroethyl) borate (TTFEB) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, the molecular sieve was added to TEP and TTFEB respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0055] (3) Weigh 29.1% KFSI, 69.9% TEP and 1% TTFEB according to the mass percentage, so that the total concentration of potassium salt in the electrolyte is 2 mol / L. Mix thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0056] Example 4 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) was selected as the phosphate ester organic solvent, and tri(2,2,2-trifluoroethyl) borate (TTFEB) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, the molecular sieve was added to TEP and TTFEB respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0057] (3) Weigh 28.8% KFSI, 69.2% TEP and 2% TTFEB according to their mass percentages to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix them thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0058] Example 5 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) solvent was selected as the organic solvent of phosphate ester, and tri(pentafluorophenyl) borate (TPFPB(Ph)) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, 3A molecular sieve was added to TEP and TFPPB (Ph) respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0059] (3) Weigh 29.4% KFSI, 70.4% TEP and 0.2% TFPPB (Ph) according to their mass percentages to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix them thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0060] Example 6 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) was selected as the organic solvent for phosphate esters, and tris(2,2,3,3-tetrafluoropropyl) borate (TTFPB) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, 3A molecular sieve was added to TEP and TTFPB respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0061] (3) Weigh 29.4% KFSI, 70.4% TEP and 0.2% TTFPB by mass percentage to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0062] Example 7 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) was selected as the organic solvent for phosphate esters, and tri(2,2,3,3,3-pentafluoropropyl) borate (TPFPB(Pr)) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, 3A molecular sieve was added to TEP and TTFEB respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0063] (3) Weigh 29.4% KFSI, 70.4% TEP and 0.2% TFPPB (Pr) according to their mass percentages to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix them thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0064] Example 8 This embodiment provides a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes, and the electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, triethyl phosphate (TEP) was selected as the organic solvent for phosphate esters, and tri(hexafluoroisopropyl) borate (THFIPB) was selected as the additive. (2) In a glove box with a humidity of less than 0.01 ppm, 3A molecular sieve was added to TEP and THFIPB respectively for dehydration and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0065] (3) Weigh 29.4% KFSI, 70.4% TEP and 0.2% THFIPB by mass percentage to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix thoroughly until completely dissolved to obtain a single salt electrolyte, which is a flame-retardant interface adaptive electrolyte suitable for carbon-based or alloy anodes.
[0066] Comparative Example 1 A potassium battery electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, diethyl carbonate (DEC) was selected as the chain carbonate organic solvent, and ethylene carbonate (EC) was selected as the cyclic carbonate organic solvent. (2) In a glove box with a humidity of less than 0.01 ppm, the molecular sieve was added to DEC and EC respectively to remove water and left to stand for 12 hours; KFSI was placed in the glove box and then dried at 80°C.
[0067] (3) Weigh out 16.1% KFSI, 48.3% EC and 35.6% DEC by mass percentage to make the total concentration of potassium salt in the electrolyte 1 mol / L. Mix thoroughly until completely dissolved to obtain comparative electrolyte 1.
[0068] Comparative Example 2 A potassium battery electrolyte is prepared according to the following steps: (1) Potassium bis(fluorosulfonyl)imide (KFSI) was selected as the main salt, and triethyl phosphate (TEP) was selected as the phosphate ester organic solvent.
[0069] (2) In a glove box with a humidity of less than 0.01 ppm, add molecular sieve to TEP for dehydration and let stand for 12 hours; place KFSI in the glove box and dry it at 80°C.
[0070] (3) Weigh 29% KFSI and 71% TEP according to their mass percentages to make the total concentration of potassium salt in the electrolyte 2 mol / L. Mix them thoroughly until completely dissolved to obtain comparative electrolyte 2.
[0071] Example 9 This embodiment provides a bismuth alloy negative electrode, which is prepared according to the following steps: (1) Bismuth nitrate (Bi(NO3)3) was selected as the bismuth salt, pyromellitic acid (C9H6O6) was selected as the organic ligand, methanol, ethanol, and N,N-dimethylformamide (DMF) were selected as the solvents, and cyanoguanidine was selected as the nitrogen-containing dopant.
[0072] (2) Weigh out 16.7% Bi(NO3)3 (150mg) and 83.3% C9H6O6 (750mg) by mass percentage, add them to a methanol:DMF mixed solution with a volume ratio of 4:1 (60ml in total), stir until clear and transparent, transfer to a 100mL hydrothermal reactor, and heat in an oven at 120℃ for 24 hours.
[0073] (3) The precursor solution obtained after the reaction was completed was washed with methanol, and the solid obtained by centrifugation was dried at 80°C. 300 mg of cyanoguanidine and the dried precursor were placed in the upstream and downstream of a tube furnace, respectively, and calcined at 800°C for 3 h under inert gas at a rate of 2°C / min. After natural cooling, the bismuth alloy anode material (Bi NPs / NC) was obtained.
[0074] (4) Mix Bi NPs / NC with conductive agent carbon black and binder CMC at a mass ratio of 7:2:1, coat evenly on copper foil, and dry to obtain bismuth alloy negative electrode.
[0075] Comparative Example 3 A carbon anode material is prepared according to the following steps: (1) Weigh an appropriate amount of perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA), place it in a tube furnace under an argon atmosphere, heat it to 900℃ at 5℃ / min and calcine for 5h, and then cool it naturally to obtain a soft carbon anode material.
[0076] (2) Mix soft carbon with conductive agent carbon black and binder CMC in a mass ratio of 7:2:1, coat evenly on copper foil, and dry to obtain soft carbon negative electrode.
[0077] Characterization and performance testing: (a) Characterization: 1. The Bi NPs / NC prepared in Example 9 were characterized, and the results are as follows: Figures 1-2 As shown.
[0078] Figure 1 The X-ray diffraction pattern indicates that the main peak in Bi NPs / NC belongs to Bi. Figure 2 The TEM images show that the highly active bismuth nanoparticles are uniformly anchored in a three-dimensional porous carbon framework.
[0079] 2. The electrolytes prepared in Example 1 and Comparative Example 2 were applied to the Bi NPs / NC prepared in Example 9. The microstructure of the electrode surface after cycling was characterized, and the results are as follows: Figures 3-4 As shown.
[0080] from Figure 3 It can be seen that the SEI film formed by the electrolyte in Comparative Example 2 has an amorphous structure and poor interfacial stability. Meanwhile... Figure 4 The addition of TTFEB to the electrolyte in Example 1 demonstrates that the SEI membrane transforms into a solid electrolyte structure rich in inorganic components. This microstructural evolution directly confirms the formation of a dense, high-performance solid electrolyte interface membrane constructed by the strong BN coordination between the electrolyte in Example 1 and the Bi NPs / NC in Example 9.
[0081] (II) Performance Testing: 1. The electrolytes prepared in Examples 1, 2, 3, 4, and Comparative Example 2 were injected into 2032 coin cell cases, with an injection volume of 100 µL. Copper foil was used as the positive electrode, and potassium metal as the negative electrode to prepare half-cells for testing. The voltage range was 0.01 V-1 V, the ambient temperature was 30 °C, and activation was performed using a 0.25 C charge-discharge cycle test. The coulombic efficiency comparison results are shown in […]. Figure 5 ; The deposition and peeling curves of K-Cu half-cells in Examples 1, 2, 3, 4, and Comparative Example 2 under the conditions of 0.01-1V, 30℃, and 0.5C charge / discharge are shown in the figure. Figure 6 ; 2. The electrolytes prepared in Comparative Example 1, Comparative Example 2, Example 1, and Example 2 were tested for battery cycle performance at 0.01-3V, 30℃, and with soft carbon material as the negative electrode. The results are shown in [Figure Number]. Figure 7 ; The charge-discharge curves of the battery prepared in Example 1 at 0.01-3V, 30℃, and with soft carbon material as the negative electrode are shown in the figure. Figure 8 ; 3. The electrolytes prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 2, Example 5, Example 6, Example 7, and Example 8 were tested for battery cycle performance at 0.01-3V, 30℃, and using Bi NPs / NC prepared in Example 9 as the negative electrode material. The results are shown in [Figure Number]. Figure 9 ; The charge-discharge curves of the battery prepared in Example 1, using the electrolyte at 0.01-3V and 30℃, with the Bi NPs / NC prepared in Example 9 as the negative electrode, are shown in the figure. Figure 10 .
[0082] 4. The comparison of the cycle performance of potassium batteries using BiNPs / NC (prepared in Example 9) and soft carbon material (Comparative Example 3) as negative electrodes under the electrolyte prepared in Example 1 at 0.01-3V, 30℃, and 50mA / g current density is shown in the figure. Figure 11 .
[0083] from Figures 5-6 It can be seen that the electrolyte prepared in Example 1 has excellent cycling performance. The K-Cu half cell made from it has a coulombic efficiency of over 99% at room temperature (30°C) and a discharge specific capacity retention rate of 98.8% after 100 cycles. The electrolytes prepared in Examples 2 to 4 also have excellent cycling performance, and the cycling performance of Examples 1 to 4 is significantly better than that of Comparative Example 2.
[0084] from Figures 7-11It can be seen that the electrolytes prepared in Examples 1-2 and 5-8, when applied to potassium batteries using Bi NPs / NC (prepared in Example 9) as the negative electrode, exhibit significantly better cycle performance than those used in potassium batteries using soft carbon materials (Comparative Example 3) as the negative electrode. This is because the electrolyte prepared in Example 1 forms a strong "BN" coordination with the Bi NPs / NC prepared in Example 9, while the soft carbon material in Comparative Example 3 does not exhibit a strong "BN" coordination with the electrolyte prepared in Example 1. Therefore, the bismuth alloy negative electrode of the present invention has a higher specific capacity and better stability than commercial soft carbon negative electrodes. Furthermore, the electrolytes prepared in Examples 1-2 and 5-8 show significantly better cycle stability and specific capacity than traditional commercial electrolytes (Comparative Examples 1-2). After 100 cycles at a current density of 50 mA / g, the discharge specific capacity in a potassium battery system using bismuth-based materials as the negative electrode is 357 mAh / g; and in a potassium battery system using soft carbon materials as the negative electrode, the discharge specific capacity is 262 mAh / g.
[0085] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A flame-retardant, interface-adaptive electrolyte suitable for carbon-based or alloy anodes, characterized in that, The electrolyte includes potassium salts, phosphate ester organic solvents, and fluoroboronic acid ester additives; The phosphate ester organic solvent contains a polar phospho group, which is used for the dissociation and coordination of potassium ions; The reduction decomposition potential of the fluorinated borate ester additive is higher than that of the phosphate ester organic solvent. In the low potential region of the negative electrode, the fluorinated borate ester additive can preferentially reduce and decompose on the carbon-based or alloy negative electrode surface to form a solid electrolyte interface film compared with the phosphate ester organic solvent.
2. The electrolyte according to claim 1, characterized in that, The potassium salt is an organic potassium salt that is a single electrolyte salt, and the anionic radius of the organic potassium salt is greater than the chloride ion radius. The potassium salt can undergo reduction decomposition on the surface of the carbon-based or alloy anode, and together with the decomposition products of the fluorinated borate ester additive, form a solid electrolyte interface film rich in inorganic components on the surface of the carbon-based or alloy anode.
3. The electrolyte according to claim 1, characterized in that, The potassium salt is selected from any one of potassium difluorosulfonylimide, potassium trifluoromethanesulfonate, potassium difluorophosphate, potassium tetrafluoroborate, potassium difluoroborate bis(oxalate) and potassium difluoroborate bis(oxalate); The general structural formula of the phosphate ester organic solvent is P(=O)-(OR3)3, wherein R3 is selected from any one of methyl, ethyl, propyl, butyl, monofluoromethyl, difluoromethyl, trifluoromethyl and phenyl; The fluorinated borate ester additives are selected from at least one of tris(hexafluoroisopropyl) borate, tris(2,2,3,3-tetrafluoropropyl) borate, tris(pentafluorophenyl) borate, tris(2,2,3,3,3-pentafluoropropyl) borate, and tris(2,2,2-trifluoroethyl) borate.
4. The electrolyte according to claim 1, characterized in that, The standard is based on the total mass of potassium salt, phosphate ester organic solvent and fluorinated borate ester additive as 100%. The mass percentage of potassium salt is 24-35 wt%, the mass percentage of phosphate ester organic solvent is 63-75 wt%, wherein the organic solvent is selected from phosphate ester organic solvent, and the mass percentage of fluorinated borate ester additive is 0.1-2.5 wt%.
5. The method for preparing the electrolyte according to any one of claims 1 to 4, characterized in that, Includes the following steps: Dehydration is achieved by using phosphate ester organic solvents and fluoroboronic acid ester additives; Dry the potassium salt at 60~80℃; The electrolyte is obtained by mixing the phosphate ester organic solvent with the potassium salt and the fluorinated borate ester additive until completely dissolved.
6. The application of the electrolyte according to any one of claims 1 to 4 in a potassium-ion battery, characterized in that, The negative electrode material of the potassium-ion battery is an alloy negative electrode material or a carbon-based material.
7. A potassium-ion battery, characterized in that, It includes a negative electrode and the electrolyte as described in any one of claims 1 to 4; The negative electrode includes a negative electrode active material, which is a bismuth nanoparticle composite material coated with a nitrogen-doped carbon network. The boron in the fluorinated borate ester additive can form a BN coordination relationship with the nitrogen in the negative electrode active material, thereby forming a solid electrolyte interface film in situ on the negative electrode surface.
8. The potassium-ion battery according to claim 7, characterized in that, The negative electrode active material is prepared by calcining a bismuth metal-organic framework precursor and a nitrogen-containing dopant under an inert atmosphere. The raw materials for preparing the bismuth metal-organic framework precursor include bismuth salts, organic ligands, and solvents. The bismuth salt is selected from at least one of bismuth nitrate, bismuth chloride, bismuth acetate, and basic bismuth carbonate; The organic ligand is selected from at least one of pyromellitic acid, terephthalic acid, 2-methylimidazolium and pyromellitic acid; The solvent is selected from at least one of methanol, ethanol, isopropanol, N,N-dimethylformamide, and N,N-dimethylacetamide; The nitrogen-containing dopant is selected from at least one of cyanoguanidine, melamine, urea, and thiourea.
9. The potassium-ion battery according to claim 8, characterized in that, In the negative electrode active material, with the total mass of the bismuth salt and organic ligand as 100%, the mass percentage of the bismuth salt is 10~25wt%, and the mass percentage of the organic ligand is 75~90wt%. The amount of nitrogen-containing dopant added is 24-48 wt% of the mass of the bismuth metal-organic framework precursor.
10. The potassium-ion battery according to claim 9, characterized in that, The preparation method of the negative electrode active material includes: mixing a solvent with a bismuth salt and an organic ligand to obtain a mixed solution; heating the mixed solution at 110~130℃ for 20~28 hours to obtain a bismuth metal-organic framework precursor; washing and drying the bismuth metal-organic framework precursor; placing a nitrogen-containing dopant and the dried bismuth metal-organic framework precursor at the upstream and downstream of a tube furnace, respectively, and calcining at 700~900℃ for 2~4 hours under an inert gas at a rate of 1~3℃ / min, followed by cooling to obtain the negative electrode active material.
